2015
DOI: 10.36076/ppj.2015/18/267
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Parecoxib and Continuous Femoral Block for Postoperative Analgesia after Total Knee Arthroplasty. A Randomized, DoubleBlind, Prospective Trial

Abstract: Background: Up until now, the optimal strategy for postoperative pain management after total knee arthroplasty (TKA) remains to be elucidated. Objective: The current investigation aimed to examine the analgesic efficacy and the opioid sparing effects of intravenous parecoxib in combination with continuous femoral blockade. Study Design: Randomized, double-blind, prospective trial. Setting: University hospital in the United Kingdom. Methods: In total, 90 patients underwent TKA under subarachnoid anesthesia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This study showed no statistically significant differences between CFNB alone and CFNB + SMI. The use of parecoxib + continuous femoral block provided superior analgesic efficacy and opioid-sparing effects in patients undergoing TKA 66 . In this context, intra-articular bupivacaine in combination with intravenous parecoxib may improve pain relief and reduce the demand for rescue analgesics in patients undergoing TKA 67 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed no statistically significant differences between CFNB alone and CFNB + SMI. The use of parecoxib + continuous femoral block provided superior analgesic efficacy and opioid-sparing effects in patients undergoing TKA 66 . In this context, intra-articular bupivacaine in combination with intravenous parecoxib may improve pain relief and reduce the demand for rescue analgesics in patients undergoing TKA 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should be conducted with different intraoperative and postoperative pain protocols to increase the antinociceptive effect potential of Mg 89 . However, RCT studies 66,67 with 44 patients reported that magnesium sulfate administration significantly reduced POP and minimized the difference in pain intensity between the first and second surgery. Another unsuccessful approach is the application of a compression dressing after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…However, from the related studies, it can be seen that the combined use of pareoxib sodium for pain relief can significantly reduce the consumption of opioids. [20][21][22][23]28,32] Orthopedic surgeons account for a large proportion of the prescription of opioids for the management of postoperative pain. How to minimize the use of opioids and effectively control postoperative pain is a long-term topic.…”
Section: Discussionmentioning
confidence: 99%
“…Bian et al [31] 66.64 ± 7.27/66.12 ± 8.34 46/42 40 mg parecoxib intravenously normal saline at the same time ①②③④ Sarridou et al [32] 70. 31 Scale scores can range from 0 to 5 points, with higher scores indicating better quality.…”
Section: ①②mentioning
confidence: 99%
“…Nonetheless, it requires an effective postoperative analgesia plan, as TKA is considered one of the most painful procedures in orthopedic surgery [3][4][5]. As much as 50% of TKA patients report severe pain after surgery, leading to prolongation of the rehabilitation period, reduced cooperation during physiotherapy sessions, and increased risk of chronic postsurgical pain development [6][7][8][9][10]. The aforementioned aspects contribute to longer hospital stays, higher costs, and an adverse socioeconomic impact [11,12].…”
Section: Introductionmentioning
confidence: 99%